Metaheurística para la colecta de residuos domiciliarios en la ciudad de Trujillo basado en el ruteo de vehículos con ventana de tiempo - Bardales Guerra, Luis Miguel (2017)
The large amount of waste produced in households worldwide is an issue that_x000D_ in recent years has become increasingly important, because of one of the factors_x000D_ causing environmental pollution is the poor collection process. There have been_x000D_ many studies to address this problem that has been increasing in recent years. One_x000D_ of them is the Vehicle Routing Problem._x000D_ The present research gave as result a vehicle routing with time windows model_x000D_ for collecting solid urban waste. Finally, due to the combinatorial nature of the_x000D_ problem, we propose a Tabu Search metaheuristic aimed at solving the presented_x000D_ problem. As case of study, the urbanizations of La Noria and El Bosque of Trujillo_x000D_ City were considered. The results obtained contribute to the reduction of operating_x000D_ costs and therefore an optimal collection of the waste for a good use later